(untitled) (Agro Productividad, 2024)
Objective: To evaluate the effect of organic fertilizers on the morphophysiological parameters and antioxidant compounds of Swiss chard (B. vulgaris L.) var. ‘Rainbow’ grown under greenhouse conditions. Design/Methodology/Approach: A completely randomized design was used with three treatments and 33 repetitions: T1 (poultry manure-based organic fertilizer (T1 AAC)), T2 (coffe pulp-based vermicompost (T2 LC)), and T3 (chemical fertilization (T3 FQ)). Plant height, stem diameter, number of leaves, leaf area, fresh biomass, dry biomass, chlorophyll A, chlorophyll B, total chlorophyll, carotenoids, total polyphenols, DPPH, and yield were evaluated. An analysis of variance and Tukey’s test (α=0.05) were used. Results: For most of the variables evaluated, the best results were obtained with the poultry manure-based organic fertilizer (T1 AAC) treatment. The antioxidant compounds and the quality of Swiss chard were influenced by organic fertilizers, with 0.21 mg Eq. gallic acid g-1 fresh tissue (ft), total chlorophyll of 19.5 µg g-1 (ft), and a yield of 6,150 kg·m2. Study Limitations/Implications: The mineral content of this vegetable was not evaluated. Findings/Conclusions: The use of poultry manure-based organic fertilizers can be an alternative nutritional management for Swiss chard cultivation.